Humanistic based Inclusive Education Management in Madrasah: Policy Review - Mu'is, Abdul; Baharun, Hasan; Suwandi, Suwandi (JURNAL AL-TANZIM, 2022)
This study aims to analyze inclusive education management policies in madrasah by applying humanistic-based learning at Madrasah Ibtidaiyah Nurus Salam. This research uses a qualitative approach. In order to get an overview of the humanistic-based inclusive education policy, the researchers conducted direct observations, interviews, and documentation. The data analysis technique is carried out circularly, from data collection, reduction, display, and conclusions. The results showed that; First, Madrasah Ibtidaiyah Nurus Salam uses inclusive education policies to accommodate students with special needs by applying humanistic-based learning. Both presentations were conducted using learning analysis, inclusive education design, implementation, and program evaluation. This study has implications for the importance of humanistic-based inclusive education in providing shelter for children with special needs so that they can develop their knowledge through existing school policies.